An exploratory study on the relationship between personal recovery and social functioning in outpatients with schizophrenia - Seiichi Watanabe; Takamichi Taniguchi; Motoko Sugihara (Hong Kong Journal of Occupational Therapy)
Objective Achieving both the social functioning and personal recovery as treatment outcomes for individuals with schizophrenia remains challenging, despite their recognition as key treatment goals beyond symptom reduction. These interrelated constructs require precise examination to inform effective rehabilitation strategies including occupational therapy. This study explores the relationships between subdomains of social functioning and personal recovery. Methods This cross-sectional study included 98 outpatients with schizophrenia. Social functioning was assessed using the Japanese version of the Specific Levels of Functioning Scale (SLOF), and personal recovery with the Japanese version of the Recovery Assessment Scale (RAS). Correlational and hierarchical multiple regression analyses examined their associations. Results The Interpersonal Relationships domain of social functioning correlated significantly with the RAS subdomains Trust in Others (r = 0.34, p < .01) and Willingness to Ask for Help (r = 0.26, p < .01). Hierarchical multiple regression analysis identified Interpersonal Relationships as a significant predictor of Trust in Others, but not Willingness to Ask for Help. Discussion These findings highlight the crucial role of interpersonal relationships in fostering trust, a key aspect of personal recovery. The results support integrated interventions addressing both social functioning and personal recovery to help reduce loneliness in individuals with schizophrenia.